2024
DOI: 10.1186/s12974-023-02996-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and inflammation cause auditory system damage via glial cell activation and dysregulated expression of gap junction proteins in an experimental model of styrene-induced oto/neurotoxicity

Fabiola Paciello,
Anna Pisani,
Rolando Rolesi
et al.

Abstract: Background Redox imbalance and inflammation have been proposed as the principal mechanisms of damage in the auditory system, resulting in functional alterations and hearing loss. Microglia and astrocytes play a crucial role in mediating oxidative/inflammatory injury in the central nervous system; however, the role of glial cells in the auditory damage is still elusive. Objectives Here we investigated glial-mediated responses to toxic injury in peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 142 publications
0
1
0
Order By: Relevance
“…These events can damage the auditory pathway, both at the peripheral (ear) and central level (brainstem and cortex) [ 60 ], resulting in SNHL. Moreover, it has been shown that the mutation of NLRP3 induces peripheral (ear) SNHL [ 61 ]. The NLRP3 inflammasome is also a key element in Alzheimer’s disease (AD); its activation induces increased synthesis of pro-IL-1β and pro-IL-18 and activates caspase-1.…”
Section: Discussionmentioning
confidence: 99%
“…These events can damage the auditory pathway, both at the peripheral (ear) and central level (brainstem and cortex) [ 60 ], resulting in SNHL. Moreover, it has been shown that the mutation of NLRP3 induces peripheral (ear) SNHL [ 61 ]. The NLRP3 inflammasome is also a key element in Alzheimer’s disease (AD); its activation induces increased synthesis of pro-IL-1β and pro-IL-18 and activates caspase-1.…”
Section: Discussionmentioning
confidence: 99%